Quality of Life of Patients After Acute Myocardial Infarction: A Scoping Review - Donny Nurhamsyah; Yanny Trisyani; Aan Nuraeni (Journal of Nursing Care, 2018)
Sudden deaths from acute myocardial infarction have been  a current trend of health care problem of Indonesians. This condition may have impacted on the patient’s quality of life. The aim of this literature review was to identify factors that affected quality of life patient after acute myocardial infarction event. This review used a scoping review method. Literature searching was conducted using Google Scholar, Pubmed and Science Direct utilizing keywords: acute myocardial infarction, quality of life and questionnaire. The inclusion criteria were quantitative or qualitative study, peer-reviewed, published in 2008 – 2018. There were 18,035 papers retreived, only 19 papers met the inclusion criteria. Data were analyzed using content analyses. The findings of this study indicate that the quality of life of patients has decreased after experiencing acute myocardial infarction. Quality of life is influenced by 5 major factors, namely biological factors, emotional factors, physical factors, social factors and psychometric factors.  There are 5 major factors that are proven to still affect the quality of life of patients with acute myocardial infarction. Further research is needed to determine psychometric factors in influencing quality of life. The instrument that can be used is macnew quality of life after myocardial infarction because it meets the psychometric criteria.